2015
DOI: 10.1080/00223891.2015.1089248
|View full text |Cite
|
Sign up to set email alerts
|

Method Effects on an Adaptation of the Rosenberg Self-Esteem Scale in Greek and the Role of Personality Traits

Abstract: Rosenberg's Self-Esteem Scale is a balanced, 10-item scale designed to be unidimensional; however, research has repeatedly shown that its factorial structure is contaminated by method effects due to item wording. Beyond the substantive self-esteem factor, 2 additional factors linked to the positive and negative wording of items have been theoretically specified and empirically supported. Initial evidence has revealed systematic relations of the 2 method factors with variables expressing approach and avoidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 71 publications
3
19
0
1
Order By: Relevance
“…In this view, in addition to the focal construct of self-esteem negatively keyed items also capture a conceptually distinct trait representing a respondent’s response consistency independent of the scales’ content. In line with this assumption, wording effects in the RSES have been found to be stable across measurement occasions (Gana et al, 2013; Marsh et al, 2010; Michaelides, Koutsogiorgi, & Panayiotou, 2016; Motl & DiStefano, 2002) and subgroups (DiStefano & Motl, 2009; Lindwall et al, 2012; Michaelides, Zenger, et al, 2016; Salerno et al, 2017), they were identified in different language versions (Tomás et al, 2013; C. H. Wu, 2008; Y.…”
Section: Are Wording Effects In the Rses More Substance Or Style?mentioning
confidence: 62%
“…In this view, in addition to the focal construct of self-esteem negatively keyed items also capture a conceptually distinct trait representing a respondent’s response consistency independent of the scales’ content. In line with this assumption, wording effects in the RSES have been found to be stable across measurement occasions (Gana et al, 2013; Marsh et al, 2010; Michaelides, Koutsogiorgi, & Panayiotou, 2016; Motl & DiStefano, 2002) and subgroups (DiStefano & Motl, 2009; Lindwall et al, 2012; Michaelides, Zenger, et al, 2016; Salerno et al, 2017), they were identified in different language versions (Tomás et al, 2013; C. H. Wu, 2008; Y.…”
Section: Are Wording Effects In the Rses More Substance Or Style?mentioning
confidence: 62%
“…Finally, although the current study has discovered individual differences in answering positively and negatively worded items, it has not examined which variables are involved. As noted earlier, several potential predictors, including personality traits, cognitive ability, reading ability, and trait anxiety have been identified (Corwyn, 2000; de Jonge & Slaets, 2005; Gnambs, & Schroeders, 2017; Marsh, 1996; Michaelides et al, 2015; Quilty et al, 2006; Roszkowski & Soven, 2010; Tomás et al, 2013). Future research could incorporate such candidate variables in FMM analysis to determine which ones best predict response inconsistency.…”
Section: Limitations and Future Researchmentioning
confidence: 86%
“…Indeed, there is some evidence that individual differences may influence the observed relationship between positively and negatively worded items. Response inconsistency has been found to be correlated with certain personality constructs (de Jonge & Slaets, 2005; Hernández, Drasgow, & González-Romá, 2004; Michaelides, Koutsogiorgi, & Panayiotou, 2015; Quilty, Oakman, & Risko, 2006). Inconsistency was also found to be associated with low cognitive ability (Gnambs & Schroeders, 2017), low reading ability (Corwyn, 2000; Marsh, 1996), and trait anxiety (Tomás, Oliver, Galiana, Sancho, & Lila, 2013).…”
Section: Negatively Worded Itemsmentioning
confidence: 99%
“…Almost universally, researchers find that a multidimensional model with two correlated factors (representing direction of wording) fits better than a “straw man” one-factor (or unidimensional) model (see Huang & Dong, 2012, for meta-analytic review). Significant debate continues, however, on whether those two factors represent distinct but highly correlated substantive dimensions of positive and negative self-appraisal (Goldsmith, 1986; Horan, DiStefano, & Motl, 2003; Kaplan & Pokorny, 1969; Michaelides, Koutsogiorgi, & Panayiotou, 2016; Owens, 1993, 1994) or are merely a direction of wording method artifact (Marsh, 1996; Tomas & Oliver, 1999) that needs to be controlled for.…”
Section: The Structure Of the Rosenberg Self-esteem Scale (Rses)mentioning
confidence: 99%